2021
DOI: 10.1051/e3sconf/202122501004
|View full text |Cite
|
Sign up to set email alerts
|

Study of internal corrosion on the turning angles in steel pipes

Abstract: Corrosive damages can lead to accidents on pipelines in various industries. Therefore, the main objective of the work is to study the peculiarities of propagation of internal corrosion on turning angles in steel pipes. The paper substantiates the primary importance of the propagation of corrosion on turning angles in steel pipes. It has been identified that in curvilinear areas, the rate of corrosion propagation depends on the rate of fluid flow, on the number of ions, and also on the effect of centrifugal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The rods were kept 28 and 60 days after the samples manufacture. The test data showed that the adhesion of the reinforcement to polymer concrete is 108 kg/cm 2 [25].…”
Section: Table 4 Abrasion Resistance Of Polymer Concrete Of Various C...mentioning
confidence: 99%
See 2 more Smart Citations
“…The rods were kept 28 and 60 days after the samples manufacture. The test data showed that the adhesion of the reinforcement to polymer concrete is 108 kg/cm 2 [25].…”
Section: Table 4 Abrasion Resistance Of Polymer Concrete Of Various C...mentioning
confidence: 99%
“…The corrosion effect of polymer concrete on steel reinforcement was studied by the following method [25]. Cube-samples were made from composition # 3 measuring 10×10×10 cm: aggregate -ground andesite and gravel with a grain size of 20-40 mm in a ratio of 1:1.5 by weight -1w.p.…”
Section: Table 4 Abrasion Resistance Of Polymer Concrete Of Various C...mentioning
confidence: 99%
See 1 more Smart Citation